Brain sodium MRI in human epilepsy: disturbances of ionic homeostasis reflect the organization of pathological regions - Ridley, Ben; Schad, Lothar R. (NeuroImage, 2017)
In light of technical advancements supporting exploration of MR signals other than 1H, sodium (23Na) has received attention as a marker of ionic homeostasis and cell viability. Here, we evaluate for the first time the possibility that 23Na-MRI is sensitive to pathological processes occurring in human epilepsy. A normative sample of 27 controls was used to normalize regions of interest (ROIs) from 1424 unique brain locales on quantitative 23Na-MRI and high-resolution 1H-MPRAGE images. ROIs were based on intracerebral electrodes in ten patients undergoing epileptic network mapping. The stereo-EEG gold standard was used to define regions as belonging to primarily epileptogenic, secondarily irritative and to non-involved regions. Estimates of total sodium concentration (TSC) on 23Na-MRI and cerebrospinal fluid (CSF) on 1H imaging were extracted for each patient ROI, and normalized against the same region in controls. ROIs with disproportionate CSF contributions (ZCSF≥1.96) were excluded. TSC levels were found to be elevated in patients relative to controls except in one patient, who suffered non-convulsive seizures during the scan, in whom we found reduced TSC levels. In the remaining patients, an ANOVA (F1100= 12.37, p<0.0001) revealed a highly significant effect of clinically-defined zones (F1100= 11.13, p<0.0001), with higher normalized TSC in the epileptogenic zone relative to both secondarily irritative (F1100= 11, p=0.0009) and non-involved regions (F1100= 17.8, p<0.0001). We provide the first non-invasive, in vivo evidence of a chronic TSC elevation alongside ZCSF levels within the normative range, associated with the epileptogenic region even during the interictal period in human epilepsy, and the possibility of reduced TSC levels due to seizure. In line with modified homeostatic mechanisms in epilepsy - including altered mechanisms underlying ionic gating, clearance and exchange - we provide the first indication of 23Na-MRI as an assay of altered sodium concentrations occurring in epilepsy associated with the organization of clinically relevant divisions of pathological cortex.
Gesehen am 12.07.2018
Available online 03 July 2017